Inflammatory hyperplasia: From diagnosis to treatment - Pradeep Shukla; Varun Dahiya; Prerna Kataria; Shreya Sabharwal (Wolters Kluwer Medknow Publications, 2014)
Gingival enlargement, the currently accepted terminology for an increase in the size of the gingiva, is a common feature of gingival disease. Local and systemic factors influence the gingival conditions of the patient. These factors results in a spectrum of diseases that can be developmental, reactive and inflammatory to neoplastic. In this article, the history, etiology, clinical and histopathological features, treatment strategies and preventive protocol of inflammatory hyperplasia are discussed.